Gray Patch Tinea Capitis Caused by Microsporum canis - Febrina Dewi Pratiwi; Trisniartami Setyaningrum (Cermin Dunia Kedokteran, 2020)
Background: Tinea capitis (TC) is the most common dermatophytosis of childhood. Case: A 3-year-old boy came with a three-week history of whitish rash and baldness. Physical examination found whitish, ill-defined patches and plaques with focal area of scaling and hyperkeratosis on the scalp (vertex region) and alopecia. Woods light examination revealed green fluorescence of infected hairs, and KOH prep revealed an ectothrix pattern of hair shaft invasion by fungal elements. Fungal growth by culture on Sabouraud dextrose agar with chloramphenicol and cycloheximide for 3 weeks found growth of M. canis. The treatment was griseofulvin 1x375 mg and ketoconazole 2% shampoo twice weekly. Complete clinical clearance was obtained after 8 weeks . Latar Belakang: Tinea Kapitis (TK) adalah dermatofitosis terbanyak pada anak. Kasus: Anak berusia 3 tahun dengan keluhan bercak putih dan botak di kepala sejak 3 minggu. Pemeriksaan fisik mendapatkan bercak keputihan, batas jelas dengan sisik tipis dan hiperkeratosis di area vertex kepala dan alopecia tanpa pustul, erosi, indurasi, atau inflamasi berat. Pemeriksaan lampu Wood menunjukkan floresensi hijau terang dan pemeriksaan KOH menunjukkan pola ectothrix elemen jamur pada sampel batang rambut. Kultur jamur pada Sabouraud dextrose agar dengan kloramfenikol dan sikloheksimid selama 3 minggu ditemukan pertumbuhan jamur Microsporum canis. Terapi griseofulvin oral 1x375 mg dan shampo ketoconazol 2% dua kali seminggu. Pasien sembuh setelah pengobatan 8 minggu.